Minding the Gap: Appraising the promise and performance of regulatory reform in Australia - Carroll, Peter (ANU Press, 2008)
'Mind the Gap!' is an almost iconic exhortation, originating in the London Underground, warning travellers to be careful when navigating the 'gap' between the platform and train. In this volume, Peter Carroll, Rex Deighton-Smith, Helen Silver and Chris Walker retrospectively assess the 'gap' - no less dynamic and perilous in a public policy context - between the promise and performance of successive waves of regulation in Australia since the 1980s. Regulatory bodies exist to exercise what might be broadly termed 'control functions' and, by nature, tend to be conservative both in their culture and operations. Institutional conservatism does not, of necessity, preclude the exercise of creativity and foresight, both of which are sorely required if government is to successfully meet the challenge of delivering more effective and less costly regulation. The business and policy environment is complex, the risks are great and the rewards of success and the costs of failure will be enormous. The true measure of success will be how effectively we are able to close the gap between promise and performance.